The role of niobium carbides in the localised corrosion initiation of 20Cr-25Ni-Nb advanced gas-cooled reactor fuel cladding - Justin Searle (Corrosion Science, 2020)
The role of niobium carbide (NbC) inclusions in directing the initiation of localised corrosion in sensitised 20Cr-25Ni-Nb stainless steel is investigated using a range of in-situ scanning techniques, allowing visualisation of corrosion behaviour over multiple length scales. Volta potential mapping shows NbC inclusions are up to 30 mV noble to the matrix, while chromium-depleted grain boundaries are up to 65 mV less noble. Corrosion initiation, shown by scanning vibrating electrode technique to comprise highly localised anode sites, is observed at grain boundaries, adjacent to the location of NbC inclusion clusters which remain unaffected by anodic dissolution of the surrounding matrix.